2005
DOI: 10.1128/iai.73.6.3577-3586.2005
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Interferon-Induced T-Cell Loss in VirulentMycobacterium aviumInfection

Abstract: Infection by virulent Mycobacterium avium caused progressive severe lymphopenia in C57BL/6 mice due to increased apoptosis rates. T-cell depletion did not occur in gamma interferon (IFN-␥)-deficient mice which showed increased T-cell numbers and proliferation; in contrast, deficiency in nitric oxide synthase 2 did not prevent T-cell loss. Although T-cell loss was IFN-␥ dependent, expression of the IFN-␥ receptor on T cells was not required for depletion. Similarly, while T-cell loss was optimal if the T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
46
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 38 publications
10
46
1
1
Order By: Relevance
“…It was shown that neutralization of IL-12 or IFN-␥ as well as depletion of CD4 ϩ T cells was able to prevent the disintegration of granulomas and the death of TNFR1-deficient mice infected with Mycobacterium avium, showing that hypersecretion of IFN-␥ by the latter T cell population may be the final mediator in the induction of this type of pathology (11). IFN-␥ has likewise been implicated as a primary mediator of other immunopathological conditions associated to chronic mycobacteriosis such as the induction of caseous necrosis in granulomas and the development of severe lymphopenia (21)(22)(23). However, the immediate effector mechanisms have not been identified for any of these phenomena.…”
Section: Characterization Of the Deregulated Immune Activationmentioning
confidence: 99%
“…It was shown that neutralization of IL-12 or IFN-␥ as well as depletion of CD4 ϩ T cells was able to prevent the disintegration of granulomas and the death of TNFR1-deficient mice infected with Mycobacterium avium, showing that hypersecretion of IFN-␥ by the latter T cell population may be the final mediator in the induction of this type of pathology (11). IFN-␥ has likewise been implicated as a primary mediator of other immunopathological conditions associated to chronic mycobacteriosis such as the induction of caseous necrosis in granulomas and the development of severe lymphopenia (21)(22)(23). However, the immediate effector mechanisms have not been identified for any of these phenomena.…”
Section: Characterization Of the Deregulated Immune Activationmentioning
confidence: 99%
“…Interestingly, infection of immunocompetent C57BL/6 mice with a high dose of the same M. avium strain did not induce necrotic granulomas. The explanation for this result lies in the fact that in this type of infection, severe lymphopenia is induced and granulomas do not get to be as large as those observed when T cells are spared, i.e., in low-dose infections (13).…”
mentioning
confidence: 97%
“…Many studies have shown that mice with a deficiency of Fas, mice lacking both Fas and TNF-␣, and mice lacking TNFR1 have impaired apoptosis or deletion of activated peripheral T cells (4 -10). Many other studies have reported normal apoptosis or deletion of activated T cells in mice with a deficiency of Fas, mice with deficiencies of both TNFR1 and Fas, and even in mice with triple deficiencies of TNFR1, Fas, and TNFR2 (11)(12)(13)(14)(15). These studies highlight a controversy about whether death receptors such as Fas and TNFR1 play essential roles during apoptosis of activated T cells.…”
mentioning
confidence: 99%